A descriptive review of next-generation insecticide-treated bed nets for malaria control - Böhmert, Antonia L.; Logan, Rhiannon A. E.; Portwood, Natalie M.; Hartke, Juliane; Ingham, Victoria A. (Frontiers in Malaria, 2024)
Insecticide treated bed nets are, to date, the most effective tool in preventing malaria related morbidity and mortality. All distributed bed nets contain pyrethroid insecticides; however, widespread resistance to this class in the malaria vectors, Anopheles spp, has led to the development of dual active ingredient bed nets, termed ‘next-generation bed nets’. These nets combine pyrethroids with a second chemistry, aimed at countering pyrethroid resistance. The World Health Organization (WHO) recently issued recommendations for three classes of next-generation bed net. In this review we will report on key indicators across Africa for each net type. The results underscore a substantial variation in key indicators across Africa when comparing next-generation bed nets to traditional pyrethroid-only nets. Nevertheless, dual active ingredient bed nets generally outperform pyrethroid-only nets in a variety of settings. The results show that new nets are a formidable tool in malaria control, with superior performance compared to traditional pyrethroid-only nets. The variability in outcomes across Africa underscores the need for a region-specific approach, fostering a targeted and adaptive strategy for the deployment of these next-generation interventions.